Hydrogen adsorption properties of carbide-derived carbons at ambient temperature and high pressure. (26th April 2021) - Naheed, Lubna; Koppel, Miriam; Paalo, Maarja; Alsabawi, Khadija; Lamb, Krystina E.; MacA. Gray, Evan; Jänes, Alar; Webb, Colin J.
Abstract: Properties of the adsorbed hydrogen phase have been studied for hydrogen adsorption in three carbide derived carbons: SiC-CDC, steam/CO2 activated SiC-CDC and TiC-CDC. Using the excess hydrogen uptake isotherm at hydrogen pressures above 120 MPa where adsorption has finished, the adsorbate volume has been determined and the adsorbate density has been calculated at ambient temperatures. Absolute adsorption isotherms have been constructed by assuming the adsorbate volume is equivalent to the pore volume and is therefore constant. This study indicates that all three CDCs had the same maximum adsorbate density, with the adsorption proportional to the total pore volume. Highlights: Synthesis of carbide-derived carbons. High pressure hydrogen adsorption isotherms up to 200 MPa at room temperature. Calculated adsorbate density from linear high pressure region of isotherm. Absolute adsorption isotherms constructed assuming that the adsorbate volume is equivalent to the pore volume. Net adsorption isotherms show the amount of hydrogen stored over that which would occupy an empty cell at the same pressure.